2020
DOI: 10.1186/s12864-020-06911-5
|View full text |Cite
|
Sign up to set email alerts
|

Wild mice with different social network sizes vary in brain gene expression

Abstract: Background: Appropriate social interactions influence animal fitness by impacting several processes, such as mating, territory defense, and offspring care. Many studies shedding light on the neurobiological underpinnings of social behavior have focused on nonapeptides (vasopressin, oxytocin, and homologues) and on sexual or parentoffspring interactions. Furthermore, animals have been studied under artificial laboratory conditions, where the consequences of behavioral responses may not be as critical as when ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 104 publications
(117 reference statements)
0
9
0
Order By: Relevance
“…A wide body of literature has demonstrated that external stimuli, such as stress, often result in significant changes in dopamine (DA) and noradrenaline (NE) concentrations in the social brain regions [2,3]. Indeed, DA neurons, located in the ventral tegmental area (VTA) and substantia nigra (SN), innervate brain regions relevant to social play and affiliative behavior, such as the prefrontal cortex, the hippocampus, the striatum and hypothalamus [4]. When subjects are in contact with social stimuli, emotional processes having a positive or negative valence involve DA neurons originating in VTA [5,6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A wide body of literature has demonstrated that external stimuli, such as stress, often result in significant changes in dopamine (DA) and noradrenaline (NE) concentrations in the social brain regions [2,3]. Indeed, DA neurons, located in the ventral tegmental area (VTA) and substantia nigra (SN), innervate brain regions relevant to social play and affiliative behavior, such as the prefrontal cortex, the hippocampus, the striatum and hypothalamus [4]. When subjects are in contact with social stimuli, emotional processes having a positive or negative valence involve DA neurons originating in VTA [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, we employed immunofluorescence to assess the expression of NET in the prefrontal cortex, hippocampus and hypothalamus, brain regions relevant to social behavior [4] where we observed altered NE levels in heterozygous DAT rats [14].…”
Section: Introductionmentioning
confidence: 99%
“…Using previously developed microdissection protocols (Horton et al . 2020), we conducted transcriptome-level sampling of the pituitary, testes, and 10 brain nuclei comprising the entire SBN and a portion of the mesolimbic reward system (MRS) (Lopes and König 2020; Bentz et al . 2021b; Kabelik et al .…”
Section: Resultsmentioning
confidence: 99%
“…Using previously developed microdissection protocols (Horton et al 2020), we conducted transcriptome-level sampling of the pituitary, testes, and 10 brain nuclei comprising the entire SBN and a portion of the mesolimbic reward system (MRS) (Lopes and König 2020;Bentz et al 2021b;Kabelik et al 2021;Bentz et al 2021a;Antunes et al 2021) (Figure 1F, Table S1.2) from nine territorial and seven floater males. A subset of these individuals were characterized for testosterone and cooperative phenotypes (Figure 1DE).…”
Section: Landscape Of Gene Expression Among Neural and Endocrine Tissuesmentioning
confidence: 99%
“…Monoaminergic activity, particularly the activity of the dopaminergic and serotonergic systems, plays a crucial role in regulating behaviour (Soares et al, 2010 ; Winberg & Thörnqvist, 2016 ). In mice, for instance, short‐term maternal separation up‐regulates drd1 in the hippocampus (Köhler et al, 2019 ), and females with smaller social networks show an up‐regulation of dopaminergic production (Lopes & König, 2020 ). Similarly to other neurological systems, during early‐life monoaminergic systems require appropriate social stimulation to achieve normal development.…”
Section: Discussionmentioning
confidence: 99%